Nutritional and nutraceutical composition of two Lamiaceae traditionally used in Portugal as spices, flavours or medicines - Fernandes, Ângela (2011)
Medicinal and aromatic plants (MAP) are highly prized in Portugal. The present work describes the study of nutritional and nutraceutical composition and the antioxidant properties of aerial parts from two Lamiaceae species.